2013
DOI: 10.1111/acps.12065
|View full text |Cite
|
Sign up to set email alerts
|

Mood instability and functional recovery in bipolar disorders

Abstract: New methodologies including subsyndromal symptoms and mood instability parameters might contribute to understand the worse long-term functional outcome that affects a considerable percentage of BD patients even after episode remission. Concerns about therapeutic approaches are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 46 publications
10
125
0
Order By: Relevance
“…It has previously been suggested that affective instability may be a core dimension of bipolar disorder, with levels being high in euthymia in comparison to controls and existing independent of manic or depressive episodes (Strejilevich et al, 2013).…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been suggested that affective instability may be a core dimension of bipolar disorder, with levels being high in euthymia in comparison to controls and existing independent of manic or depressive episodes (Strejilevich et al, 2013).…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%
“…Whilst affective instability is transdiagnostic (Broome et al, 2015b) our findings add further support to the idea that affective instability may be a particularly important psychopathology in bipolar disorder. It may underlie some of the severe consequences of the illness, predicting chronicity and severity in youth with the disorder (Yen et al, 2015) and functional losses in those with established illness (Strejilevich et al, 2013).…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Presence of depressive symptoms is associated with worse outcomes. 8 Cognitive impairments in BD are consistently observed during mood episodes. [9][10][11][12] However, they can also be identified during euthymia.…”
Section: Introductionmentioning
confidence: 99%
“…Mood instability and interpersonal sensitivity are typical characteristics of BD [1][2][3][4] . In comparison to other mood and anxiety disorders, patients with BD suffer from a greater severity of disability [5] .…”
Section: Introductionmentioning
confidence: 99%